2019
DOI: 10.2298/bah1904335y
|View full text |Cite
|
Sign up to set email alerts
|

Typological assessment of dairy farms systems in semi-arid Mediterranean region of Western Algeria

Abstract: The present study aimed to characterize the dairy cattle farming systems in semi arid region in western Algeria. A typology of the farms was established following the description of livestock dairy farming practices and the assessment of their contribution to farm efficiency. The enquiry was conducted on 60 dairy farms during 2018-2019 agricultural campaign to determine structural, technical and economic parameters. The Results show a large diversity of farmer?s strategies, particularly in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 2 publications
1
13
0
1
Order By: Relevance
“…In addition, the average production cost of one kg of milk is 35 AD / kg. This cost is similar to that reported by Yerou et al (2019) in the western region of Algeria, which is 37.1 AD/kg. Farmers of type 5 (more affluent) report the lowest cost of production compared to other groups at only 27.5 AD/kg.…”
Section: Economic Performance Of Dairy Cattle Farmssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the average production cost of one kg of milk is 35 AD / kg. This cost is similar to that reported by Yerou et al (2019) in the western region of Algeria, which is 37.1 AD/kg. Farmers of type 5 (more affluent) report the lowest cost of production compared to other groups at only 27.5 AD/kg.…”
Section: Economic Performance Of Dairy Cattle Farmssupporting
confidence: 90%
“…In the same study area but in 2007, Kadi et al (2007a reported that this amount could reach 10 kg/cow/day. In the western region, Yerou et al (2019) report that the concentrate distribution varies from 5.5 to 10 kg/cow/day. But in the eastern region of India, Gupta el al.…”
Section: Animals Feedingmentioning
confidence: 99%
“…However, categorical variables were later used to further characterize obtained clusters or production systems. PCA was used to combine variables into a smaller number of factors [71,72] as well as CA classified farmers into specific heterogenous clusters that were also homogeneous within [73]. To perform PCA, Kaiser-Meyer-Olkin (KMO) and Bartlett sphericity tests were used to check whether the dataset of 471 farm households and 13 variables were appropriate for PCA.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The upper critical temperature for cows is 25 to 26 oC (Bonmanova et al, 2007); cows decrease milk production when THI exceeds the critical comfort zone of 72. In Algeria, the technical and economic results of the dairy performance of dairy farms are weak despite the existence of an improved breed of livestock imported from abroad (Yerou et al,2019). Exotic breed of cows like Holstein are universally classified as high yielding, in a semi-arid Algerian environment, they produce below their expected levels of performance during lactation in their country of origin (Kaouche et al 2015 andYerou et al, 2019).…”
Section: Characterization Of Microclimatic Conditionsmentioning
confidence: 99%
“…Studies on the evolution of performance in dairy cattle farming have shown that the effect of the environment combined with breeding practices leads to a drop in body weight and the level of milk production. Typological studies indicate the limits of a model based on a large-format exogenous breed, transferred to semi-arid regions to improve milk production (Yerou et al ., 2019). In addition, the results show the need for a debate on the model of dairy farming in arid and semi-arid dairy farms in Mediterranean regions, as well as on the role that the selection of local breeds can have in such conditions.…”
Section: Introductionmentioning
confidence: 99%